Semantic Based Intelligent Information Retrieval through Data mining and Ontology - Ahmed, Muqeem (International Journal of Computer Sciences and Engineering, 2025)
On the Web and other document repositories the amount of content stored and shared keeps increasing steadily and fast that results in well known difficulties and problems when it comes to finding and properly managing information in massive volumes. In the last decade with the development of search engine technologies Striking progress has been achieved, which collect, store and pre-process information worldwide to return relevant resources instantly in response to users’ needs. However, users still miss or need considerable effort sometimes to reach their targets, even if the sought information is present in the search space. Currently consolidated content description and query processing techniques for Information Retrieval are based on keywords, and therefore provide limited capabilities to grasp and exploit the conceptualizations involved in user needs and content meanings are the common caust. This involves limitations such as the inability to describe relations between search terms to solve the limitations of keyword based , the idea of concept based information retrieval ,conceptual search, understood as searching or retrieving by meanings rather than keyword or literal strings, has been the focus of a wide body of research in the information retrieval field. The semantic technologies such as XML and ontology can play important role for the development of semantic based information retrieval. This paper is an attempt to develop semantic based Information Retrieval for the exploitation of domain knowledge to support semantic information retrieval search capabilities in large document repositories more intelligently; it explores the use of semantic technologies such as xml and ontology to support more expressive queries and more accurate results. for this we have collected the documents from the different domains and design the tree structures of the documents in the form of xml and ontology and data mining technique such as clustering and then retrieve the information from this structure based on user interest that provide the concept based.